2021
DOI: 10.3389/fpsyt.2021.677136
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Symptoms Are Associated With Higher Psychological Stress, Poor Sleep, and Inadequate Sleep Hygiene in Collegiate Young Adults—A Cross-Sectional Study

Abstract: Background: Anxiety symptoms, stress, poor sleep, and inadequate sleep hygiene are common in university students and these affect their learning and increase attrition. However, limited knowledge exists about the inter-relationship between these factors among university students in low-middle income countries. Therefore, this study aimed to investigate the prevalence of anxiety symptoms and their relationship with sleep quality, sleep hygiene practices, and psychological stress.Materials and Methods: A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Second, with regard to psychological aspects, compared with the staff in low-risk areas, the staff exposed to the high-risk setting and having a direct contact with a significant number of infected people, may have greater concerns about exposure to infection coupled with the patient's negative emotions, protective material shortage, lack of contact with family, and guilt from not being able to save each patient, leading to a significant increase in the psychological pressure of frontline staff ( 20 , 26 ). Research has revealed that psychological stress is directly related to mental health problems such as anxiety and insomnia, and the greater the psychological stress, the higher the likelihood of these symptoms ( 45 , 48 , 49 ). The European Psychiatric Association also issued a statement highlighting the necessity of paying attention to psychological problems and early intervention among frontline workers ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, with regard to psychological aspects, compared with the staff in low-risk areas, the staff exposed to the high-risk setting and having a direct contact with a significant number of infected people, may have greater concerns about exposure to infection coupled with the patient's negative emotions, protective material shortage, lack of contact with family, and guilt from not being able to save each patient, leading to a significant increase in the psychological pressure of frontline staff ( 20 , 26 ). Research has revealed that psychological stress is directly related to mental health problems such as anxiety and insomnia, and the greater the psychological stress, the higher the likelihood of these symptoms ( 45 , 48 , 49 ). The European Psychiatric Association also issued a statement highlighting the necessity of paying attention to psychological problems and early intervention among frontline workers ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“… 76 Since we did not collect the nature, severity, and type of stress or anxiety, it was difficult to evaluate whether these students had higher levels of anxiety or stress before the COVID-19 pandemic, or whether stress or anxiety increased due to COVID-19 pandemic as a result of social distancing, reduced family support, or fear of getting infected. 77 More recently, Manzar et al 78 have discovered a link between insufficient sleep hygiene habits and anxiety levels among university students. In contrast to current findings, a past study conducted in Malaysia found no significant correlation between ethnicity and anxiety, depression, or stress in university students.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of stress is associated with an increased risk of developing several pathologies, including sleep disorders and psychiatric diseases ( 6 , 7 ). More than 60% of patients with generalized anxiety disorder have insomnia symptoms, with increased wakefulness, reduced sleep amount, and less slow-wave sleep ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%